Technological and Research Alliances as a Competitive advantage for Nissan and Renault - Liu, Aicanzi (2008)
Globalization makes the world smaller and smaller. (Meredith & Shafer, 2001). The products and services in the world provide by firms on the basis of globalization. Especially in the last decade, it is noted that the changes accelerated the globalization pace dramatically and increased the resource, money, culture, and business interaction. Exactly under the results of changes and the formation of more and more global market, the strategic alliance gains its rapid development among the companies. Strategic alliances in today are increasingly popular across the national borders in order to gain the fast and economical growth. More and more multi-national firms such as Google, Microsoft, IBM and Nissan, etc, are busy to looking for their global strategic alliances in order to improve their global competitive ability and leverage their partner firms competencies. These companies consider it as an important source of resources, learning and more important to the competencies improvement. Recent researches demonstrated that the number of alliances is growing with an high average rate of 25 percent per year ((Parise, S. & Casher, A., 2003). It is said that the strategic alliance is a by-products of the economic globalization in today's business environment.